The Occurrence of Autophagic Cell Death in the Tegument of Rabbits Pre-Infested with Rhipicephalus sanguineus and Exposed to Selamectin (Active Principle of Acaricide Pfizer Revolution (R)) - Bozzatto, Vlamir [UNESP]; De Oliveira, PatrICia Rosa [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2013)
Ticks of Rhipicephalus sanguineus species have great medical and veterinary importance for being a vector of various diseases. In an attempt to minimize their action on the host, people have resorted to chemical control by using various acaricides, such as selamectin. Although previous studies have demonstrated its toxic action in domestic animals, no studies focused on the detection of cell death when exposed to selamectin. For this reason, the technique for detecting autophagic cell death was used in order to demonstrate the responses of rabbits' skin tissues pre-infested with R. sanguineus and exposed to different concentrations of selamectin. The obtained results when exposed to 100 and 80% concentrations of selamectin showed a strong mark of acid phosphatase on the cells of the connective tissue of the dermis and hair follicles, whereas the ones exposed to the 50% concentration had a weak mark on the cells of the connective tissue of the dermis and moderate staining in hair follicles. It became clear that, when used at high concentrations (100 and 80%), selamectin is capable to induce a large scale occurrence of the autophagic cell death process. On the other hand, the concentration of 50% causes minor morphophysiological changes in the skin of rabbit hosts when evaluated the cell death process. Therefore, the data confirms that selamectin is a powerful dose-dependent toxic agent causes increased activity of the enzyme acid phosphatase. Microsc. Res. Tech. 76:1171-1176, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: acid phosphatase; acid hydrolases; autophagy; infestation; toxicology